88.8k views
0 votes
What are the full steps to 7x(x-2)+5(x-3)=-5

User Leiaz
by
5.7k points

2 Answers

3 votes

Answer:

Brianliest!

Explanation:

simplify

7x^2-14x+5x-15 = -5

7x^2 - 9x - 10

x= 1

x = -0.7142857143

User Niaz
by
6.5k points
5 votes

Answer:


x = -(5)/(7), 2

Explanation:

To solve this equation, we need to simplify it down first. To do this, we must apply the distributive property to each term.


7x(x-2) + 5(x-3) = -5\\\\(7x^2 - 14x) + (5x - 15) = -5

Now we can combine like terms.


7x^2 - 9x - 15 = -5

Add 5 to both sides:


7x^2 -9x - 10 = 0

We can see that this is a quadratic equation, in the form
ax^2 + bx + c. To solve for x, we must use the Quadratic Formula, which is
(-b\pm√(b^2-4ac))/(2a), where a is 7, b is -9, and c is -10.

Substitute inside the equation:


(-(-9)\pm√(-9^2-4\cdot7\cdot-10))/(2\cdot7)\\\\(9\pm√(81+280))/(14)\\\\(9\pm19)/(14)\\\\(9+ 19)/14 = 2\\\\(9 - 19)/14 = -(5)/(7)

Hope this helped!

User Regent
by
6.4k points